Let it snow : three holiday romances - Green, John, 1977-; Johnson, Maureen, 1973-; Myracle, Lauren, 1969- (New York : Speak, 2008)
In three intertwining short stories, several high school couples experience the trials and tribulations along with the joys of romance during a Christmas Eve snowstorm in a small town.
The Jubilee express / Maureen Johnson -- A cheertastic Christmas miracle / John Green -- The patron saint of pigs / Lauren Myracle.
014-017.
Keywords: Dating (Social customs) -- Juvenile fiction; Christmas stories; Short stories, American; Dating (social customs) -- Fiction; Christmas -- Fiction; Interpersonal relations -- Fiction; Storms -- Fiction; Short stories; Young adult fiction